Balls, Barbecues and Boxing: Contesting gender regimes at organizational social events. Issue 1 (January 2019) - Ortlieb, Renate; Sieben, Barbara
What do the relaxed social events held by companies and organizations do for continued gender inequality? This article argues that outings, barbecues and parties offer opportunities for members of an organization to challenge unequal gender regimes. But they can also end up maintaining these inequalities instead. The article draws on Joan Acker's theory of gendered organizations, and Judith Butler's notion of gender performativity. Based on 208 accounts of organizations' social events, it identifies the following four areas of gender performativity and their varying significance in reaffirming or challenging unequal gender regimes: gender images, status differences, the body and sexuality. The findings indicate that practices reaffirming unequal gender regimes outnumber practices that possibly balance or break them. Paradoxically, practices that challenge unequal gender regimes, when joined with powerful responses from the hitherto privileged party, can form a vicious circle which again ends up continuing unequal gender regimes. The article provides a more nuanced understanding of ambivalences and the contested nature of gender regimes which is important in identifying avenues for gender equality.